-1-m=6m-29

Simple and best practice solution for -1-m=6m-29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1-m=6m-29 equation:


m in (-oo:+oo)

-m-1 = 6*m-29 // - 6*m-29

29-m-(6*m)-1 = 0

29-m-6*m-1 = 0

28-7*m = 0 // - 28

-7*m = -28 // : -7

m = -28/(-7)

m = 4

m = 4

See similar equations:

| -4x+3=9+2x | | 6a+6=18+3a | | -2x-5=-6x+35 | | -a-3=-27+5a | | 5x-3=7x+13 | | -b-9=-4b+6 | | -3d+5=2d-45 | | -4d+5=4d-59 | | -3+3a=-2a+22 | | 2n-2=-7n+106 | | 7d+5=53+3d | | -a+1=-11+5a | | a-6=-14-3a | | 7t-4=68-5t | | 7d+5=11+6d | | 4(2y-y)=6(2y+8) | | Ax+bc=d | | 2a-5=7a-5 | | -6w+2=7w+145 | | 1+n=-5n+7 | | 3k+7=9+k | | -4k+7=2k+55 | | 5b-8=6b-4 | | k-7=7k+5 | | 3+4p=-7 | | Dx=p | | 3x+20=12x+88 | | -4+d=-3d+8 | | 2-4k=-6k+18 | | -5a+5=23-7a | | 7k+6=-2k+60 | | 9.67-4.33y=-3.8y+0.1z |

Equations solver categories